2014
DOI: 10.1155/2014/738921
|View full text |Cite
|
Sign up to set email alerts
|

Hole-Phonon Relaxation and Photocatalytic Properties of Titanium Dioxide and Zinc Oxide: First-Principles Approach

Abstract: First-principles calculations for the temporal characteristics of hole-phonon relaxation in the valence band of titanium dioxide and zinc oxide have been performed. A first-principles method for the calculations of the quasistationary distribution function of holes has been developed. The results show that the quasistationary distribution of the holes in TiO2extends to an energy level approximately 1 eV below the top of the valence band. This conclusion in turn helps to elucidate the origin of the spectral dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 27 publications
3
21
0
Order By: Relevance
“…The validity of the 'effective phonon' approach is well confirmed by means of comparing this data with the results of the 'exact' calculations obtained with such an approximation avoided [23,24]. We see in figure 2 that for both electrons and holes the correspondence between the results of these two approaches is almost perfect.…”
Section: Definitions and Justificationsupporting
confidence: 66%
See 4 more Smart Citations
“…The validity of the 'effective phonon' approach is well confirmed by means of comparing this data with the results of the 'exact' calculations obtained with such an approximation avoided [23,24]. We see in figure 2 that for both electrons and holes the correspondence between the results of these two approaches is almost perfect.…”
Section: Definitions and Justificationsupporting
confidence: 66%
“…According to (18) the average value of energy loss by an electron in the single electron-phonon scattering act becomes independent of the excess energy level ε av (E) = ε 0 . In our calculations [12,22,23] we have shown that for realistic band structures in ZnO and TiO 2 this quantity ε av (E) manifests a weak dependence versus E, both for electrons and holes, see figure 1. Similarly the quantity…”
Section: Definitions and Justificationmentioning
confidence: 89%
See 3 more Smart Citations